Super-oxide anion production and antioxidant enzymatic activities associated with the executive functions in peripheral blood mononuclear cells of healthy adult samples. (May 2016) - Pesce, M.; Rizzuto, A.; La Fratta, I.; Tatangelo, R.; Campagna, G.; Iannasso, M.; Ferrone, A.; Franceschelli, S.; Speranza, L.; Patruno, A.; De Lutiis, M.A.; Felaco, M.; et al.
Highlights: Oxidative metabolism is associated with executive functions. PBMCs superoxide anion production is negatively related to executive functions. Peripheral GPx and CAT enzymatic activities are correlated to executive functions. Abstract: Executive Functions (EFs) involve a set of high cognitive abilities impairment which have been successfully related to a redox omeostasis imbalance in several psychiatric disorders. Firstly, we aimed to investigate the relationship between executive functioning and some oxidative metabolism parameters in Peripheral Blood Mononuclear Cells (PBMCs) from healthy adult samples. The Brown Attention-Deficit Disorder Scales were administered to assess five specific facets of executive functioning. Total superoxide anion production, Super Oxide Dismutase (SOD), Catalase (CAT), Glutathione Reductase (GR) and Glutathione Peroxidase (GPx) activities were evaluated on proteins extracted from the PBMCs. We found significant positive correlations between superoxide anion production and the total score of the 'Brown' Scale and some of its clusters. The GPx and CAT activities were negatively associated with the total score and some clusters. In a linear regression analysis, these biological variables were indicated as the most salient predictors of the total score, explaining the 24% variance (adjusted R (2) = 0.24, ANOVA, p  < .001). This study provides novel evidence that Executive Functions have underpinnings in the oxidative metabolism, as ascertained in healthy subjects.